2021
DOI: 10.7150/ijms.63402
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis identified shared differentially expressed genes as potential biomarkers for Hashimoto's thyroiditis-related papillary thyroid cancer

Abstract: Background: Although the etiology of Hashimoto's thyroiditis (HT), a common autoimmune endocrine disease, is unknown, studies suggest a potential association with genetic factors and environmental conditions inducing excessive iodine intake. Additionally, HT patients have a high risk of papillary thyroid cancer (PTC), which is probably related to the chronic inflammation and autoimmune pathologic process occurring in HT, as it is thought to be associated with neoplastic transformation. Methods: Bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…The present study also investigated whether CCL21 and ZCCHC12 were common down- or upregulated genes, respectively, in the 4 subclusters. The results supported evidence from previous observations, including those of Liu et al , who found that the expression of CCL21 is lower in PTC tissues than in Hashimoto’s thyroiditis tissues ( 31 ), and Smallridge et al , who reported that CCL21 is associated with lymphocyte infiltration and is differentially overexpressed in BRAF-wild-type tumors compared to BRAF V600E-mutation-harboring tumors ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…The present study also investigated whether CCL21 and ZCCHC12 were common down- or upregulated genes, respectively, in the 4 subclusters. The results supported evidence from previous observations, including those of Liu et al , who found that the expression of CCL21 is lower in PTC tissues than in Hashimoto’s thyroiditis tissues ( 31 ), and Smallridge et al , who reported that CCL21 is associated with lymphocyte infiltration and is differentially overexpressed in BRAF-wild-type tumors compared to BRAF V600E-mutation-harboring tumors ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…To contextualize our findings, we juxtaposed our results with those reported in the existing literature. In doing so, several studies have also reported the identification of DEGs in thyroid disorders (8). For instance, He et al, identified a similar number of DEGs in a transcriptome analysis of thyroid cancer patients, highlighting the consistency with our findings (9).…”
Section: Discussionsupporting
confidence: 87%
“…SERPINA1, a protein associated with inflammatory disease, organismal injury, and abnormal thyroid function, is significantly lower in hyperthyroidism samples than in normal thyroid samples ( 64 , 65 ). As a hub gene for PTC-DEGs, SERPINA1 is potential diagnostic gene for PTC and is related to the extracellular matrix pathway ( 66 68 ). Our findings further suggest that SERPINA1 serves as an important cross-linking gene involved in the pathogenesis of HT and PTC.…”
Section: Discussionmentioning
confidence: 99%